Operation procedure of sacrococcygeal fetus in fetu - Rochadi Rochadi (Paediatrica Indonesiana, 2011)
Fetus in fetu is a condition in wich a fetiform calcified mass often presents in the abdomen of its host, a newborn. It is extremely rare condition, estimated once in 500,000 deliveries and has a 2: 1 male predominantly; with most patient presenting with an abdominal Â mass in the first year of life. 5,13 The term fetus in fetu is used to point out an unequal division of totipotential cells of blastocyst where the result is the inclusion of a small cellular mass in the more mature embryo. It was encapsulated, pedunculated and represents a malformed monozygotic, monochorionic, diamniotic parasitic twin. In 80% cases, fetus in fetu is located Â retroperitonealy but can be found in unusual location such as in oropharynx, neck, skull mediastinum, pelvis, iliac mesentery, adrenal gland, sacrococcygeal region and scrotal sac.